Analysis of Marketing Mix Strategies with a SWOT Approach in Increasing Market Competitiveness at Coffee Shop De'ale Sidoarjo - Dinda Larasati Esa Putri; Yanda Bara Kusuma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to evaluate Coffee Shop De'Ale's marketing mix strategy to improve its competitiveness in the coffee industry. This research uses a qualitative descriptive approach and uses SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis to identify the strengths, weaknesses, opportunities, and threats faced by De'Ale. The analysis results show that De'Ale is in quadrant I in the SWOT matrix, indicating that an aggressive growth strategy is the most suitable for the current situation. Therefore, De'Ale should expand its cafe area, increase its digital promotion through social media such as Instagram and TikTok, and cooperate with influencers or food bloggers to expand the market. By implementing these strategies, De'Ale is expected to become more competitive in the growing coffee industry.